A long-term and comprehensive assessment of urbanization-induced impacts on ecosystem services in the capital city of India. (August 2020) - Sharma, Sonali; Nahid, Shadman; Sharma, Mani; Sannigrahi, Srikanta; Anees, Mangalasseril Mohammad; Sharma, Richa; Shekhar, Ravi; Basu, Arunima Sarkar; Pilla, Francesco; Basu, Bidroha; Joshi, P.K.
Abstract: Globally, the present rate of urbanization in mega-urban centers is altering ecosystem functions and resultant ecosystem services of the landscapes. The natural and semi-natural ecosystems within the urban regions are under threat of loss and degradation. Estimating the economic values of the ecosystem services obtained from these natural and semi-natural ecosystems can play an important role in urban policy and decision making. The main objective of this paper is to quantify the changes in ecosystem service values (ESVs) in response to land use land cover (LULC) dynamics and urbanization in the capital city of India, Delhi. Using satellite imageries over the past two decades (1998–2018) we show the estimated changes in ESVs with the global value coefficient (VC) of proximate biomes. The study relies on benefit transfer approach of ESs valuation wherein the ESVs of proximate biomes, derived from one/multiple study site, are used in assessing ESVs at another site. For determining the reliability of the study, a sensitivity analysis is performed to check the effectiveness of VC. The results show a total decline of ecosystem services (ESs) in monetary terms by US$ 7.614 million ha −1  year −1 from 1998 to 2018 with prominent changes in LULC. The change analysis shows a loss (US$ 3.6141 million) of regulatory and provisional services. The prominent part (US$ 2.675 million) of this loss was due to decline in city forest cover by 6426.09 ha. The city has benefitted from initiatives in implementation of biodiversity parks and plantation drives, but also suffers widespread loss of forest over the years. The ESs monitoring at the city administrative divisions (i.e. district-wise) highlights the importance of conservation of natural ecosystems within the urban area with distribution equity. The results provide insights that should be considered for urban planning in order to protect natural resources, ESs, and thus overall well-being of residents. Highlights: The natural and semi-natural ecosystems within the urban regions are under threat of loss and degradation. This study examined the response of ecosystem services (ESs) to land use land cover (LULC) changes in Delhi, India. Regulating and provisioning services have exhibited a trade-off association with urbanization. Total decline of ESs in monetary terms was estimated as US$ 7.614 million from 1998 to 2018.